LUT BASED FREDKIN GATE - Tyurin, S. F. (Radio Electronics, Computer Science, Control, 2020)
Context. The concept of existing computers when achieving nanoscale hardware has almost exhausted itself. This also applies to computing power and related energy costs. Reversible computing, for example billiard-ball computer, is the base model of the quantum computing which are considered to be the prospect of IT technology. Billiard-ball computing is energy-effective computing or green computing. Base of such paradigm are special logic gates. However, the mathematical apparatus for creating such computers has not yet been fully developed. The problem is that for new reversible elements that have a one-to-one correspondence between inputs and outputs, the application of well-known methods of analysis and synthesis encounters certain difficulties. So, for example, it is forbidden to use branching, which significantly complicates the synthesis. Reversible elements should provide signal transmission in the forward and reverse directions, which is in principle feasible in binary logic based on tri-states buffers, but significantly complicates the device, increases the crystal area and power consumption, which they are designed to reduce. Objective. The goal of the work is the analysis of the functionally complete reversible gates that named Toffoli gate, Fredkin gate, the analysis of the binary full adder, based on Fredkin gates and to design method for circuits based proposed gate. Methods. Analysis of the digital circuits with Boolean algebra. Synthesis digital circuits with proposed decomposition method. Design Fredkin gate in term of the FPGA’s Look up Table. Simulation of proposed element in the system NI Multisim by National Instruments Electronics Workbench Group. Results. Analysis of the full adder based on Fredkin gates. Synthesis method of the reversible circuits based on Fredkin gates. LUT based Fredkin gate and it simulation. Conclusions. The conducted studies allows us to build circuits based on Fredkin gates from proposed novel elements.